A deep First-Order System Least Squares method for solving elliptic PDEs. (1st January 2023) - Bersetche, Francisco M.; Borthagaray, Juan Pablo
Abstract: We propose a First-Order System Least Squares (FOSLS) method based on deep-learning for numerically solving second-order elliptic PDEs. The method we propose is capable of dealing with either variational and non-variational problems, and because of its meshless nature, it can also deal with problems posed in high-dimensional domains. We prove the Γ-convergence of the neural network approximation towards the solution of the continuous problem and extend the convergence proof to some well-known related methods. Finally, we present several numerical examples illustrating the performance of our discretization.